Buginese Migrants in Historical Narratives: A Historiographical Critique - Umar Umar (Retorik: Jurnal Ilmu Humaniora)
Buginese migrants are present in various historical narratives. Every historian also has a different way of presenting their narrating process. Those historical narratives gave birth to various notions of Buginese migrants. One of the notions often attributed by historians to Buginese migrants is that their lives are almost always associated with the sea. The purpose of this research is to examine how historians present Buginese migrants in their historical narratives. This research uses the historical narrative research model developed by Hayden White. There are three concepts elaborated by Hayden White used in this study, namely, the concepts of “representation,” “individual,” and “morals.” These concepts are theoretical tools for analyzing four historical texts about Buginese migrants. The results of these analyses become a historiographical critique. This research found that every historian has a different identification of Buginese migrants in each of their narratives. The Buginese people in Johor are identified as closely connected with power by Kesuma. Buginese people in Bali are associated with trade by Suwitha. The Buginese people in Kamal Muara are closely associated with fishermen by Said and Prabowo. Lastly, Buginese people in Ambon are associated with Islam by Soleh. Each historian has a different position in narrating Buginese migrants. Their tendencies are affected by their own background.